Concurrent Validity of the Child Occupational Self-Assessment in Children with Attention Deficit Hyperactivity Disorder - Mahsa Sattari; Seyed Ali Hosseini; Mehdi Rassafiani; Mina Ahmadi-Kahjoogh (Vesnu Publications, 2016)
Introduction: Independency in daily activities is one of the first achievements in childhood that can help the child promote his/her sense of independency and socialization. In this study, concurrent validity of the Child Occupational Self-Assessment (COSA) and the Pediatric Quality of Life Inventory, which evaluate daily activities, was assessed in children with attention deficit hyperactivity disorder (ADHD). Materials and Methods: This correlational study was conducted on 128 children with ADHD. Data analysis was performed and correlation coefficients were reported using SPSS software. Results: The highest correlation coefficient was that of the total competency and child quality of life (QOL) score (r = 0.566) and the lowest was that of social performance competency score (r = -0.444) (P < 0.01). The highest and lowest correlation coefficients in the value subscale were, respectively, that of the total child QOL score (r = -0.46) and emotional performance (r = -0.347) (P < 0.01). Conclusion: Based on the findings of this study, the COSA has an acceptable concurrent validity with the Pediatric Quality of Life Inventory, and thus, can be used for the assessment of children with ADHD.